2017
DOI: 10.1177/0145561319889538
|View full text |Cite
|
Sign up to set email alerts
|

In-Office vs. Operating Room Procedures for Recurrent Respiratory Papillomatosis

Abstract: We conducted a study to analyze hospital and patient costs, outcomes, and patient satisfaction among adults undergoing in-office and operating room procedures for the treatment of recurrent respiratory papillomatosis. Our final study population was made up of 17 patients—1 man and 16 women, aged 30 to 86 years (mean: 62). The mean number of in-office laser procedures per patient was 4.2, and the mean interval between procedures was 5.4 months (although 10 patients underwent only 1 office procedure); the mean n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…The weighted mean time interval between OR-based procedures was 10.59 months (95% CI 5.83-15.35, n = 2, I 2 = 49%, τ 2 = 6.9391, P = .16). Only Miller et al 17 reported the time interval between office procedures, which was 5.40 months with 95% CI (3.26, 7.54). Reasons for reintervention included bulky disease requiring subsequent OR surgery, 21 recurrence, 33 or repeat operation for otherwise unspecified reason, 30 but there was no mention of staged procedures affecting the inter-operative interval.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The weighted mean time interval between OR-based procedures was 10.59 months (95% CI 5.83-15.35, n = 2, I 2 = 49%, τ 2 = 6.9391, P = .16). Only Miller et al 17 reported the time interval between office procedures, which was 5.40 months with 95% CI (3.26, 7.54). Reasons for reintervention included bulky disease requiring subsequent OR surgery, 21 recurrence, 33 or repeat operation for otherwise unspecified reason, 30 but there was no mention of staged procedures affecting the inter-operative interval.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 studies, only one 17 directly compared operative in-office treatment to OR treatment of RRP, analyzing the number of procedures, time interval between procedures, complications, and cost between the two treatment settings. Another study 18 compared cost between office and OR.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations